The Application of Artificial Intelligence as Evidence in the Court - Perbawa, I Ketut Sukewati Lanang Putra (International Journal of Social Science and Business, 2021)
Revolution Industry 4.0 is one of the biggest era in this century, because in this era the big technological development happening around the world with some of the creation is Artificial Intelligence. Artificial Intelligence is one of the technology that exist in the world and can resembles like a human in the other hand Artificial Intelligence can do what actually human do for example Learning, Planning, Critical Thinking, Problem Solving, any many more. Therefore several countries using it in the court. Artificial Intelligence use it as evidence to prove some case and made prosecutor, judge and lawyer easier to work. However, in Indonesia there wasnâ€™t the law about Artificial Intelligence therefore it would be difficult to use it in the court as evidence because according to several sources in procedural law there are some valid evidence that can only use in the court. However, the crime that happen in Indonesia usually related to technology made all the government have to forming the law about the Artificial Intelligence.Â